2022
DOI: 10.1001/jama.2022.1025
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intra-arrest Transport, Extracorporeal Cardiopulmonary Resuscitation, and Immediate Invasive Assessment and Treatment on Functional Neurologic Outcome in Refractory Out-of-Hospital Cardiac Arrest

Abstract: Key PointsQuestionIn patients with witnessed refractory out-of-hospital cardiac arrest, does early intra-arrest transport, extracorporeal cardiopulmonary resuscitation, and invasive assessment and treatment improve outcomes compared with standard resuscitation?FindingsIn this randomized clinical trial that included 256 patients, survival with neurologically favorable outcome (Cerebral Performance Category 1-2) at 180 days occurred in 31.5% in the invasive strategy group and 22.0% in the standard resuscitation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
227
1
10

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 344 publications
(284 citation statements)
references
References 36 publications
7
227
1
10
Order By: Relevance
“…Our group has very recently published a randomized controlled trial encompassing ECPR which clearly showed its enormous potential to rescue patients that might have been pronounced dead without an ECPR availability. 5 And finally, our group presented an extraordinary case report in the current issue on dual veno-arterial ECMO in a patient with refractory hyperdynamic septic shock. 6 This report nicely shows the type of thinking necessary for running a comprehensive ECMO program-an out-of-the-box approach.…”
Section: Honest Cooperation Is a Futurementioning
confidence: 94%
See 1 more Smart Citation
“…Our group has very recently published a randomized controlled trial encompassing ECPR which clearly showed its enormous potential to rescue patients that might have been pronounced dead without an ECPR availability. 5 And finally, our group presented an extraordinary case report in the current issue on dual veno-arterial ECMO in a patient with refractory hyperdynamic septic shock. 6 This report nicely shows the type of thinking necessary for running a comprehensive ECMO program-an out-of-the-box approach.…”
Section: Honest Cooperation Is a Futurementioning
confidence: 94%
“…Our group has very recently published a randomized controlled trial encompassing ECPR which clearly showed its enormous potential to rescue patients that might have been pronounced dead without an ECPR availability. 5…”
mentioning
confidence: 99%
“…In einer zweiten randomisierten kontrollierte Studie von Bělohlávek et al. an Patienten mit OHCA und vermuteter kardialer Genese zeigte eCPR im Vergleich mit cCPR einen Trend zu besserem neurologischem Überleben, jedoch ohne statistisch signifikanten Unterschied (31,5 % vs. 22,0 %; p = 0,09; [ 8 ]). Im Unterschied zu Yannopoulos et al.…”
Section: Evidenz Und Outcomeunclassified
“…2 zeigt häufige Einschlusskriterien in eCPR-Studien, deren prospektive Evaluierung steht allerdings noch aus. Der Anteil der potenziellen eCPR-Patienten im HKS-Gesamtkollektiv wird zwischen 6 und 11 % angegeben [ 8 , 22 ]. Durch die Seltenheit wird der frühzeitigen und akkuraten Identifikation dieser Patienten auf allen Ebenen der Versorgung, beginnend bei der Rettungsleitstelle über den Rettungsdienst bis zur aufnehmenden Klinik, eine tragende Rolle zuteil.…”
Section: Patientenselektionunclassified
See 1 more Smart Citation